In-office Customized Brackets: Aligning with the Future - Nearchos C. Panayi (Galenos Yayinevi, 2023)
Digital technology introduced many innovations in the field of dentistry and orthodontics in the last years. The most important advancement was the ability to digitize the oral cavity using intraoral scanners. CAD software have been around for decades, but only in the last twenty years started showing up in the field of dentistry and orthodontics. 3D printers are not new in the field of manufacturing. Nevertheless, their inclusion in the orthodontist armamentarium was made possible only the last few years, while new printing materials have been also invented, allowing the manufacturing of many appliances previously made using traditional laboratory procedures. Orthodontic treatment is mainly based on the use of fixed appliances. The vast majority of orthodontists use commercial straight-wire brackets while customized brackets are preferred mostly for lingual orthodontic treatment. New CAD software called Ubrackets allows the in-office designing and printing of customized brackets using hybrid ceramic crown resin or zirconia slurry. Some scientific studies have been conducted to investigate the bracket printing outcome in terms of mechanical properties. More studies must be performed to allow the inclusion of in-office designing and printing of customized brackets in the orthodontic armamentarium.